Exoskeleton plantarflexion assistance for elderly - Galle, S.; Derave, W.; Bossuyt, F.; Calders, P.; Malcolm, P.; De Clercq, D. (Gait & posture, 2017)
•Generally, physically active elderly (over 65y) can walk with an exoskeleton that assists push-off.•The exoskeleton reduced metabolic cost with 12% compared to powered-off. Elderly are confronted with reduced physical capabilities and increased metabolic energy cost of walking. Exoskeletons that assist walking have the potential to restore walking capacity by reducing the metabolic cost of walking. However, it is unclear if current exoskeletons can reduce energy cost in elderly. Our goal was to study the effect of an exoskeleton that assists plantarflexion during push-off on the metabolic energy cost of walking in physically active and healthy elderly. Seven elderly (age 69.3±3.5y) walked on treadmill (1.11ms2) with normal shoes and with the exoskeleton both powered (with assistance) and powered-off (without assistance). After 20min of habituation on a prior day and 5min on the test day, subjects were able to walk with the exoskeleton and assistance of the exoskeleton resulted in a reduction in metabolic cost of 12% versus walking with the exoskeleton powered-off. Walking with the exoskeleton was perceived less fatiguing for the muscles compared to normal walking. Assistance resulted in a statistically nonsignificant reduction in metabolic cost of 4% versus walking with normal shoes, likely due to the penalty of wearing the exoskeleton powered-off. Also, exoskeleton mechanical power was relatively low compared to previously identified optimal assistance magnitude in young adults. Future exoskeleton research should focus on further optimizing exoskeleton assistance for specific populations and on considerate integration of exoskeletons in rehabilitation or in daily life. As such, exoskeletons should allow people to walk longer or faster than without assistance and could result in an increase in physical activity and resulting health benefits.